Econometrics and Reality - Kevin Hoover (University of California, Department of Economics, 1997)
Starting with a realist ontology the economic methodologist, Tony Lawson, argues that econometrics is a failed project. Apparently more sympathetic to econometrics, the philosopher of science, Nancy Cartwright, again from a realist perspective, nonetheless argues for conditions of applicability that are so stringent that she must seriously doubt the usefulness of econometrics. In this paper, I reconsider Lawson''s and Cartwright''s analyses and argue that realism supports rather than undermines econometrics properly interpreted and executed.
Keywords: 330